8-Thia-1,6-diazabicyclo[4.3.0]nonane-7,9-dione - Xi, Bin-bin (International Union of Crystallography, 2011)
There are two independent molecules, A and B, in the asymmetric unit of the title compound, C(6)H(8)N(2)O(2)S. In the crystal, pairs of intermolecular S⋯O contacts [3.286 (1) Å] link the B molecules into inversion dimers.